New insights into the photocatalytic endocrine disruptors dimethyl phathalate esters degradation by UV/MWCNTs-TiO2 nanocomposites - Tan, Tong Ling; Lai, Chin Wei; Hong, Sok Lai; Abdul Rashid, Suraya (Elsevier BV, 2018)
Dimethyl phthalate esters (DMPEs) are considered to be endocrine disruptors and environmentally hazardous materials in plastic industries wastewater because of its low solubility and accumulated persistent toxicity. In the present study, MWCNTs/TiO2 nanocomposites were fabricated by modified sol-gel technique using titanium isopropoxide as titanium oxide sources and purified MWCNTs, to degrade DMPEs through photocatalysis using UV irradiation. The effect of MWCNTs loading (3–15 wt %) on TiO2 and the photocatalytic performance of DMPEs in aqueous solution by UV/MWCNTs/TiO2 nanocomposites were investigated. For experiments conducted with the same illumination time, the photodegradration of DMPEs was enhanced with increasing the MWCNTs contents from 3 to 10 wt % and then decreased with a further enhancement to 15 wt %. Basically, the presence of MWCNTs in the nanocomposites can lead to the decrease in the relative amount of TiO2 in the photocatalyst and then to the decrease of the photogenerated carriers. This is because the same amount of photocatalyst was added for the photoreaction, and hence, the photodegradation of DMPEs decreases especially for the nanocomposites containing MWCNTs exceed than 10 wt %. The presence of functional group (COOH) on the MWCNTs surface would help the achievement of direct chemical bonding between MWCNTs and the TiO2 nanoparticles, resulting in the synergistic effect of MWCNTs and TiO2 where the flow of photogenerated electrons in the space charge region to the MWCNTs surface. A method based on high-performance liquid chromatography (HPLC) was developed to study the degraded DMPEs samples produced after exposure to UV light.